Structure-activity and structure-selectivity studies on diaminoquinazolines and other inhibitors of Pneumocystis carinii and Toxoplasma gondii dihydrofolate reductase. - Rosowsky, A (1995)
Twenty-eight 2,4-diaminopteridines with alkyl and aralkyl groups at the 6- and 7-positions, five 1,3-diamino-7,8,9,10-tetrahydropyrimido [4,5-c]isoquinolines with an alkyl, alkylthio, or aryl group at the 6-position, and nine 4,6-diamino-1,2-dihydro-s-triazines with one or two alkyl groups at the 2-position and a substituted phenyl or naphthyl group at the 1-position were evaluated as inhibitors of dihydrofolate reductase enzymes from Pneumocystis carinii, Toxoplasma gondii, and rat liver. Halogen substitution at the 5- or 6-position of 2,4-diaminoquinazoline favored selective binding to the P. carinii enzyme but not the T. gondii enzyme. For example, the 50% inhibitory concentrations of 2,4-diamino-6-chloroquinazoline as an inhibitor of P. carinii, T. gondii, and rat liver dihydrofolate reductase were 3.6, 14 and 29 microM, respectively, corresponding to 12-fold selectivity for the P. carinii enzyme but only marginal selectivity for the T. gondii enzyme. Greater than fivefold selectivity for P. carinii but not T. gondii dihydrofolate reductase was also observed for the 2,4-diaminoquinazolines with 5-methyl, 5-fluoro, 5- and 6-bromo, 6-chloro, and 5-chloro-6-bromo substitution. In contrast, alkyl and aralkyl substitution at the 6- and 7-positions of 2,4-diaminopteridines was found to be a favorable feature for selective inhibition of the T. gondii enzyme and, in two cases, for both enzymes. Nine of the fifty-one compounds tested against P. carinii dihydrofolate reductase and four of the thirty compounds tested against T. gondii dihydrofolate reductase displayed fivefold or greater selectivity for the microbial enzyme versus the rat liver enzyme. The most selective against both enzymes was 2,4-diamino-6,7-bis(cyclohexylmethyl) pteridine, with a selectivity ratio 2 orders of magnitude greater than the value reported for trimetrexate and piritrexim. Since substitution at the 7-position is generally considered to be detrimental to the binding of 2,4-diaminop-teridines and related compounds to mammalian dihydrofolate reductase, the selectivity observed in this study with the 6,7-bis(cyclohexylmethyl) analog may represent a useful approach to enhancing selective inhibition of the enzyme from nonmammalian species.